2023
DOI: 10.3390/su151813925
|View full text |Cite
|
Sign up to set email alerts
|

Can Unveiling the Relationship between Nutritional Literacy and Sustainable Eating Behaviors Survive Our Future?

Hande Mortaş,
Semra Navruz-Varlı,
Merve Esra Çıtar-Dazıroğlu
et al.

Abstract: The primary objective of this study was to explore the relationship between food and nutrition literacy and sustainable, healthy eating behaviors among young adults. This cross-sectional study took place in Ankara, the capital city of Turkey, involving 500 participants (265 females, 235 males) whose average age was 22.6 ± 3.97 years. A questionnaire was administered through face-to-face interviews, covering three sections: (1) general information, (2) the food and nutrition literacy instrument (FNLI), and (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(46 reference statements)
2
3
0
Order By: Relevance
“…This means that every individual with a level of nutrition knowledge has a more fantastic option of making informed decisions and ratifying his or her decision, even when external pressures seek to be against healthy food choices. Furthermore, other research that supports this study indicates that nutritional literacy is an indicator that influences behavior and decisions regarding food consumption ( 142 , 143 ).…”
Section: Discussionsupporting
confidence: 75%
“…This means that every individual with a level of nutrition knowledge has a more fantastic option of making informed decisions and ratifying his or her decision, even when external pressures seek to be against healthy food choices. Furthermore, other research that supports this study indicates that nutritional literacy is an indicator that influences behavior and decisions regarding food consumption ( 142 , 143 ).…”
Section: Discussionsupporting
confidence: 75%
“…On the contrary, two other components, namely, food preparation skills and social and conscious eating, had no positive impact on ecological eating behavior [70]. A similar result was obtained in a cross-sectional study involving young adults in the city of Ankara (Turkey), which determined a relationship between food and nutritional literacy and sustainable eating behaviors [71]. A significant correlation was found between the depth of knowledge, attitude, and behavior linked to food and nutritional knowledge and the tendency to embrace more A recent study examined the link between the food literacy of South Korean university students and ecological eating behavior towards sustainability.…”
Section: Relation Between Food/nutrition Literacy and The Environmentsupporting
confidence: 67%
“…Mortaş et al [71] 2023 Relationship between food and nutritional literacy and sustainable eating behaviors.…”
Section: Zhu Et Al [69] 2023mentioning
confidence: 99%
“…Finally, it was confirmed that S-NutLit is a reduced scale and applicable in the Peruvian context, and its reliability indicators are within the determined ranges and divided into two factors: informational skills (α = 0.83) and expert skills (α = 0.79), which makes the instrument a valid metric. In this regard, theoretical foundations have been identified that support that informational and expert skills are part of nutritional literacy, described as the ability of an individual to obtain, understand, and comprehend nutritional information, which leads to improvement of an individual’s behavior towards informed and healthy eating [ 1 , 74 ]. Thus, the division of the factors allows a better view of the multidimensional nature of the construct, which shows that beyond the population’s knowledge of nutritional information, it also extends to knowing how to interpret and apply it in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…As a product of this study, it has been suggested that the nutritional literacy scale (S-NutLit) in the Peruvian context promotes the improvement of quality of life, a healthy diet, and the development of good eating habits. In addition, the results of this study suggest that improving nutritional literacy could prevent health risks and complications (diabetes, malnutrition, insufficient intake, and poor quality of life), leading to a modification of one’s lifestyle to prevent the onset and progression of these health disorders [ 23 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%